2015
DOI: 10.1055/s-0035-1554928
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Human Ovarian Follicular Dynamics

Abstract: Inflammation is a biologic process that mediates tissue effects including vasodilation, hyperemia, edema, collagenolysis and cell proliferation through complex immunologic pathways. In regards to the ovary, inflammation has key physiologic roles in ovarian folliculogenesis and ovulation. On the other hand inflammatory processes are subject to underlying pathology and if pushed, proinflammatory conditions may have a negative impact on ovarian follicular dynamics. Obesity and polycystic ovary syndrome (PCOS) ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
114
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(118 citation statements)
references
References 53 publications
2
114
0
2
Order By: Relevance
“…When oocytes are exposed to an aged ovarian microenvironment, they themselves will undergo a process of reproductive aging (Tatone et al ., ). Inflammatory cytokines constitute one of the most potent factors in the ovarian microenvironment that are involved in physiologic and pathologic processes within the ovary (Boots & Jungheim, ), and recent studies have shown effects of inflammatory conditions on ovarian reserve in women (Freour et al ., ). Elevated levels of pro‐inflammatory factors, including IL‐1β and TNF‐α (tumor necrosis factor‐a), have been reported to be associated with poor oocyte quality and negative effects on IVF outcomes (Lee et al ., ; Revelli et al ., ; Winger et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…When oocytes are exposed to an aged ovarian microenvironment, they themselves will undergo a process of reproductive aging (Tatone et al ., ). Inflammatory cytokines constitute one of the most potent factors in the ovarian microenvironment that are involved in physiologic and pathologic processes within the ovary (Boots & Jungheim, ), and recent studies have shown effects of inflammatory conditions on ovarian reserve in women (Freour et al ., ). Elevated levels of pro‐inflammatory factors, including IL‐1β and TNF‐α (tumor necrosis factor‐a), have been reported to be associated with poor oocyte quality and negative effects on IVF outcomes (Lee et al ., ; Revelli et al ., ; Winger et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in human fibroblast culture indicate that MMP3 expression is exclusively regulated by HIF1A in response to inflammation that suggests that metalloproteinases expression is involved in follicular rupture (Ahn et al, 2008). It is well known that inflammation is a key component of the ovulation process (Boots and Jungheim, 2015;Espey et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that PCOS share similar properties with many chronic inflammatory disorders, and classical inflammatory mediators such as C-reactive protein (CRP), tumor necrosis factor-α (TNF-α) and interleukin-6 (IL- 6) have also been found to be elevated in patients with PCOS [9][10][11]. Moreover, pro-inflammatory cytokines and its associated over-activated immune responses have also been shown to be associated with higher androgen levels, and have been shown to be able to impact ovarian function and jeopardize the processes of ovulation in PCOS [12,13]. Therefore, if a polymorphism can impact gene expression or the protein structure of cytokines, it is highly likely that it might alter inflammation status and influence predisposition to PCOS.…”
mentioning
confidence: 99%